SPEECH ACTS USED BY MIA DOLAN IN â€œLA LA LANDâ€ MOVIE - Bernadia Lupita Wirastri; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2017)
The research belongs to discourse analysis because the data are in the forms of words and sentences. The procedures of the research were: (1) identifying the utterances expressed by Mia Dolan by watching the movie and comparing the dialog of the movie with the movie script taken from internet, (2) classifying and analyzing data based on types and functions of speech act, presenting data in the table, and (3) describing and discussing the finding in the form of description based on the table of an analysis of speech act. The findings of this research show there are 209 utterances of speech act. From the five categories of speech acts, there are only four categories used by Mia Dolan; they are representative (99 data or 45.45%). The functions are:Â stating, affirming, predicting, retelling, calling, answering, concluding, reporting, complaining and informing. There are 68 data of directives (32.53%) and the functions are: questioning, commanding, warning, suggesting and requesting. Expressive speech act reaches 34 data (16.26%) and the functions are: apologizing, thanking, expressing feeling, expressing pleasure, expressing pain, complimenting and greeting. Commisive reaches 12 data (5.74%), the functions are: promising, refusing, offering and threatening. Declarative is not used by Mia Dolan.